Pemetaan Masalah Belajar Siswa SMK Negeri 3 Yogyakarta Dan Penyelesaiannya (Tinjauan Srata Kelas) - Bastomi, Hasan (IAIN Kudus, 2020)
Mapping Of Problem Learning Problem Vocational School 3 Yogyakarta And Its Completion (Class Srata Review). This study aims to uncover the mapping of students' learning problems at SMK Negeri 3 Yogyakarta and their resolution is reviewed from the classroom. Research on student learning problems was conducted using a qualitative approach with a survey method with a sample size of 292 for an error rate of 5%. The instrument used in uncovering student learning problems is a non-test instrument check list problem (DCM) and an open questionnaire for how to solve problems then analyzed with descriptive analysis. The results showed that students of SMK Negeri 3 Yogyakarta experienced learning problems with a process of more than 90% with class XII having the biggest learning problems with a process of 96%, class XI students at 95% and class X students at 92%. The factors that cause learning problems in SMKN 3 Yogyakarta students are the lack of students' ability to manage time, technological development so that learning time is spent playing games and social media, as well as the tight hours of study of SMK students. Learning problem solving by students of SMKN 3 Yogyakarta there are various styles of problem solving including; trying to solve problems, seek social support, with religion and unproductive solutions.Keywords: Problems, Learning, Settlement